Factors Behind the Establishment and Fulfillment of Norway-Indonesia REDD+ Partnership (2010-2019) - Lioretta Wijaya; Witri Elvianti (Kajian Asia Pasifik, 2022)
The concentration of Greenhouse Gas (GHG) emissions creates non-boundary effects. Fighting the problem requires cooperation among states. As a developed country, Norway has continuously shown its support towards the addressing ecological issues both domestically and globally. The government actively engages in international environmental discussion and amplifies its status in the forum through financial contribution and consultation. As part of the Norway’s environmental diplomacy to be a global environmental leader, the country actively offers a partnership to developing countries with forest problems, including Indonesia, through Norway-Indonesia REDD+ partnership. By using the International Cooperation and Domestic Political Institution theories, this research aims to identify the factor behind the establishment and fulfilment of Norway-Indonesia REDD+ bilateral agreement. Ultimately, the study finds that the confidences that Norwegian government has towards Indonesia’s commitment on emission reduction pushes the offering of the partnership from the Norwegian government. Furthermore, the funds promised under the agreement attracts Indonesia to enter the agreement and fulfill it as it helps the country to achieve its forest-related emission reduction goals.